Noah : a play - Obey, André, 1892-1975 (French's standard library edition., 1962)
"Noah, his wife, his three sons and three of the neighbors' girls embark with the animals on God's ark. When the rain ends, the grand beauty of the great waters fills them with rejoicing and they dance around the deck in the dawn of a golden age. But Ham, the canker of the old world, has crept on board. He doubts. He taunts his shipmates with old misgivings and Noah becomes the story of a kindly old man who grows lonely in his faith, who pilots his craft safely to shore in the midst of doubts, and who is rudely deserted by the young folks the moment they touch foot to land. Noah shouts at the heavens, "Are you satisfied? The answer is a rainbow in the sky."--Publisher's description.